URGENSI PENDIDIKAN KELUARGA DI MASA PANDEMI COVID-19 - Rizaludin Kurniawan; Margono Mitrohardjono; Adi Fahrudin (Universitas Muhammadiyah Jakarta, 2021)
Pandemi Covid-19 menyebabkan dikeluarkannya berbagai kebijakan dari pemerintah. Salah satu kebijakan tersebut adalah kebijakan Belajar Dari Rumah serta Bekerja Dari Rumah. Dalam karya ilmiah ini dipaparkan mengenai urgensi pendidikan keluarga di masa pandemi Covid-19 kaitannya dengan kebijakan Belajar Dari Rumah serta Bekerja Dari Rumah. Karya ilmiah ini menyuguhkan suatu kesimpulan bahwa urgensi pendidikan keluarga di masa pandemi Covid-19 tersebut diwujudkan melalui optimalisasi fungsi orang tua dalam mendidik anak selama proses Belajar Dari Rumah di masa pandemi Covid-19 berlangsung notabene menjadikan orang tua sebagai mentor anak di rumah serta orang tua sebagai pendidik karakter anak.ABSTRACTThe covid-19 pandemic led to the issuance of various policies from the government. One of these policies is the Study From Home and Work From Home policy. This scientific paper describes the urgency of family education during the Covid-19 pandemic in relation to the policy of Learning from Home and Working from Home. This scientific work presents a conclusion that the urgency of family education during the Covid-19 pandemic was realized through optimizing the function of parents in educating children during the Learning From Home process during the Covid-19 pandemic which makes parents as mentors of children at home and parents as educators of children's character.Keyword: Education, Family, Pandemic of Covid-19